ANALISIS PENYAJIAN LAPORAN KEUANGAN BERDASARKAN PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) PADA PT. NUANSA DHARMA CIPTA - E Y Suharyono 3, Gisela Imelda Florensia Eka Yudhyani 2 (EKONOMIA, 2021)
ABSTRACTFinancial reports are a very important tool for obtaining information about a company's financial position. Financial reports should be a necessity for every business unit, especially for business owners, given the benefits for business continuity. The object of this research is PT. Nuansa Dharma Cipta is a trading company in Samarinda City. PT. Nuansa Dharma Cipta is one of the entities without public accountability.This study uses a qualitative descriptive study with a case study method that compares the financial statements of PT. Nuansa Dharma Cipta with components of SAK ETAP accounting standard posts. The steps taken to obtain data and information are observation and documentation. Data analysis was performed by comparing the components in SAK ETAP. The hypothesis presented is that the components of financial statements, balance sheet items and income statements are not in accordance with SAK ETAP.The conclusion of the study that the financial statements of PT. Nuansa Dharma Cipta only met 12 of the total 25 recommendations for Financial Accounting Standards for Entities Without Public Accountability, making the conformity rate 48%. So that it can be judged that it is not in accordance with SAK ETAP, the hypothesis that was previously proposed is accepted.Â